Human Resource Development in Increasing Work Productivity - Husain, Fransiska; Yulia, Rasty; Syaifudin, Arif; Karyadi, Sugeng; Alatas, Abd. Rahman (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Human resources have a major role in every organizational activity. As the main key, human resources will determine the success of the implementation of organizational activities. Human resources always play an active and dominant role in every organization, because human resources are planners, actors and determinants of the realization of organizational goals. A productive person describes the potential, perception and creativity of a person who always wants to contribute his abilities to benefit himself and his environment. The aim of this research is to explain human resource development in increasing work productivity. To help answer questions about human resource development in increasing work productivity, the type of research is theoretical research with the help of secondary sources such as books or journals.